A biocompatible dual-AIEgen system without spectral overlap for quantitation of microbial viability and monitoring of biofilm formation. Issue 6 (23rd April 2021) - He, Wei; Zheng, Zheng; Bai, Haotian; Xiong, Ling-Hong; Wang, Lei; Li, Yinghui; Kwok, Ryan T. K.; Lam, Jacky W. Y.; Hu, Qinghua; Cheng, Jinquan; Tang, Ben Zhong
Abstract : A dual-AIEgen system for microbial imaging and metabolic status sensing has been realized through chemistry strategies. This dual-AIEgen system can detect general microbes and identify their viabilities as well as their microbial biofilms. Abstract : The lack of rapid and reliable microbial detection and sensing platforms and insufficient understanding of microbial behavior may delay precautions that could be made, which is a great threat to human life and increases the heavy financial burden on society. In this contribution, a dual-aggregation-induced emission luminogen (AIEgen) system is successfully developed for microbial imaging and metabolic status sensing. This system consists of two AIEgens (DCQA and TPE-2BA) that bear positively charged groups or boronic acid groups, providing universal microbial staining ability and specific affinity for dead microbes, respectively. Based on the distinctive fluorescence response produced by the diverse interaction of AIEgens with live or dead microbes, this dual-AIEgen system can detect all the microbes and identify their viabilities. Furthermore, the morphology and metabolic status of a sessile biofilm can also be imaged and monitored. The system exhibits rapid labelling properties that suitable for various microbes, and good biocompatibilities.